Repercussões da disfunção vestibular no convívio familiar e social de idosos - Oliveira, Renata Porcel de (2008)
The research "Implications of vestibular dysfunction in the family and social coexistence of elderly" wide knowledge relevant to the interfaces between the areas of Social Gerontology and Health The central objective of this study is to examine the influences of the involvement of vestibular dysfunction by elderly people in their conviviality family and social relationships, seeking help in this segment can live fully the stage of old age and have a treatment with quality. The development of concepts concerning the anatomy and physiology of the vestibular system, as well as the understanding of possible malfunctions causing these diseases, particularly noted in the ageing process, are addressed recital is a broad concept of health. The search was conducted of field through the application of interviews involving nine elderly people aged over 65 years, which have the vestibular dysfunction, receive emergency medical care and carry out physiotherapy home with professionals in MEDMAR / FAMILY The Emergency Medical Service, located in the city of Santos, in the State of Sao Paulo. These elderly live with their families, which were also interviewed. Bringing up procedures methodological own qualitative research was done, initially, the characterization of the stage of vestibular dysfunction of the subject, based on existing medical diagnoses. Through semistructured guide, proceeded to the identification of the condition of personal life and family and social coexistence, before and after the onset of the disease. Data analysis shows that the vestibular dysfunction should be conceived as one of the constituent elements of the ageing process and that the symptoms of manifestation of this involvement must be properly understood and cares for the elderly by it and by their relatives, considering the impact recognized in depositions, both in family and social coexistence